The dark ages - Sitko, Joseph (Colorado : Chariot [production company] ; Illinois : AGC/United Learning [distributor], 1995)
Part one it will shows how Britain was changed when it became a province of Rome and also discover what happened when Aglo-Saxons destroyed Roman civilization in Britain and Rome's unified government was replaced by many small warlike kingdoms. Part two shows the reintroduction of Christianity into Britain and discover the roles played by two important seventh-century saints in bringing this about
Narrator: Lois La Fond
Keywords: Europe -- History -- 392-814; Middle Ages -- History